Exploring Soundscape Perception in the Historical Catur Gatra Tunggal Area, Kotagede, through the Soundwalk - Kusumawardani, Neni; Marcillia, Syam Rachma (Universitas Islam Sultan Agung Semarang, 2025)
Kotagede Yogyakarta is a historical area left behind by the Islamic Mataram Kingdom. Now that district developing into a residential area. This area has a legacy of Javanese spatial structure and spatial pattern known as the concept of